Miniaturized rotating magnetic field–driven plasma system: proof-of-concept experiments. (1st June 2021) - Sun, Y; Levchenko, I; Lim, J W M; Xu, L; Huang, S; Zhang, Z; Thio, F; Potrivitu, G-C; Rohaizat, M W A B; Cherkun, O; Chan, C S; Baranov, O; et al.
Abstract: The development of plasma-based propulsion thrusters for spacecraft has seen a rapid growth over the past few decades, with the number of spacecraft including small satellites and Cubesats increasing exponentially. Although traditional chemical propulsion is still widely employed in space flights, it cannot meet the more challenging requirements for deep space travel due to low specific impulse. Electric propulsion thrusters have already helped humans travel further from Earth and have the potential to be developed for interstellar flights due to their advantages such as high velocity increments, long operational lifetimes, high impulse-to-weight ratios and high impulse-to-power ratios. The electrodynamic thrusters have significant potential for applications in the remote regions of space, and several types of electrodynamic plasma thrusters are currently under investigation. In this paper we present conceptual experiments to study a miniaturized Rotamak-type device initially proposed for the controlled thermonuclear fusion, with a view to assess its potential for the application as a small space thruster . An outline of the physical characteristics of the experiments that has been carried out, and measurements were done to try to elucidate the important mechanisms at work in the Rotamak, which will help design next-generation thruster capabilities. A discussion is also presented about the Rotamak systems and the opportunities they present for space applications.